Peran Anggota Keluarga dalam Proses Pembelajaran Siswa SDN 03 Kuamang Nagari Panti Timur Kabupaten Pasaman - Nelvia Aprinalni; Nurlizawati Nurlizawati (Naradidik: Journal of Education and Pedagogy, 2022)
The role of parents is needed during the learning process at home. The role of parents is also very much needed for the education process for students who still cannot understand the material given by the teacher at school. This study aims to analyze the role of family members during the learning process. This research is a qualitative type with data collection techniques used through observation, interviews and documentation. The role of family members during the learning process of students at SDN 03 Kuamang Nagari Panti Timur Pasaman Regency uses the theory of voluntary social action initiated by Talcott Parson. Research informants obtained from the results of the study amounted to 13 people. The data analysis used in this research from Milles and Huberman is data reduction, data presentation and conclusion drawing. The results of the study Based on the results of research that has been carried out related to the title "The Role of Family Members in the Learning Process of SDN 03 Students" it can be concluded that there are several roles that parents must replace the teacher's position when studying at home which include: giving direction or supervision to teach children, providing direction to children for tutoring or tutoring, providing adequate facilities and infrastructure to complete learning facilities, taking work time to assist children in learning.